D-learning model on Physics Instrumentation Course for Optimizing Performance Skills - Agus Suyatna; Viyanti Viyanti; Doni Andra; Ismi Rakhmawati (Jurnal Pembelajaran Fisika, 2021)
The COVID-19 pandemic has forced the implementation of lectures at universities to be fully carried out online or distance learning (d-learning). On the course that have sub- learning achievements of performance assessment, they experience many obstacles in achieving the learning objectives of that domain. The purpose of this study was to develop an online d-learning model for the Physics Instrumentation course based on Moodle that was valid to optimize performance skills, effective, and have high practicality for students of the Physics Education Study Program. The research method used R&D. The development procedure was carried out based on the ADDIE model covering five main activity stages, which are analysis, design, development, implementation, and evaluation. In this article, is reported until development stage. Data was collected using a questionnaire distributed using google forms. Data analysis included needs analysis, design suitability test, content/material test, construct test, language, and product readability test. The results of this study concluded that online d-learning model based on Moodle for Physics Instrumentation course was valid for optimizing the performance skills of students of the Physics Education Study Program because it had learning activities of reading e-Modules, watch videos of practice procedures and how to use measuring instruments, performing measurement simulations using virtual instruments, working on the task of making simple instruments with stages of activities according to the Engineering Design Process (EDP) model, discussing procedures for using the most appropriate measuring instruments, self-reflection on the materials that have and not been mastered and follow-up plans.Keywords: d-learning; performance assessment; moodle based; physics instrumentationDOI: http://dx.doi.org/10.23960/jpf.v9.n2.202103